Antioxidant Activity of Red Ginger Extract (Zingiber officinale, var. Rubrum) Using Microwave-Assisted Extraction (MAE) Method - Mulyadi, Arie Febrianto; Novenlintyas, Allisa Azhara Juang; Sukardi, Sukardi (Department of Agro-industrial Technology, University of Brawijaya, 2025)
AbstractThe non-volatile components of red ginger that have antioxidant properties are gingerol, shogaol, and zingerone compounds. The antioxidant activity of red ginger is very strong, with an IC50 value of 25.69 ppm. These compounds can be obtained through an extraction process. Microwave-Assisted Extraction (MAE) is an extraction method that combines microwave radiation with heat to efficiently and effectively extract active compounds from the material. This study investigated the extraction of red ginger using variations in two factors: power (100, 400, and 600 W) and extraction time (2, 4, and 6 minutes). The response variables measured were antioxidant activity (IC50), total phenols, and yield. The study used a Randomized Block Design with ANOVA as the data analysis method, followed by the Least Significant Difference test with a 5% confidence interval. The results showed that the red ginger extraction process using MAE with microwave power treatment and extraction time significantly affected the parameters of yield, total phenols, antioxidant activity, and moisture content. The best treatment results were obtained with a microwave power of 400 W and an extraction time of 2 minutes, which produced 25.7% yield, 5.7 mg GAE/g total phenol content, a 39 ppm antioxidant activity (IC50), and 72.4% of moisture content.Keywords: antioxidant, extraction, microwave-assisted extraction, red ginger AbstrakKomponen non volatil pada jahe merah yang memiliki kemampuan sebagai antioksidan adalah senyawa gingerol, shogaol, dan zingeron. Aktivitas antioksidan pada jahe merah sangat kuat dengan nilai IC50 sebesar 25,69 ppm. Senyawa tersebut dapat diperoleh melalui proses ekstraksi. Microwave-Assisted Extraction (MAE) merupakan salah satu metode ekstraksi yang menggabungkan radiasi microwave dengan panas untuk mengekstrak senyawa aktif pada bahan secara efisien dan efektif. Penelitian ini melakukan ekstraksi jahe merah menggunakan variasi terhadap dua faktor, yaitu daya (100, 400, dan 600 W) dan waktu ekstraksi (2, 4, dan 6 menit). Variabel respon yang diukur adalah aktivitas antioksidan (IC50), total fenol, dan rendemen. Penelitian menggunakan Rancangan Acak Kelompok dengan ANOVA sebagai metode analisis data kemudian dilanjutkan dengan uji Beda Nyata Terkecil dengan selang kepercayaan 5%. Hasil penelitian menunjukkan bahwa proses ekstraksi jahe merah menggunakan MAE dengan perlakuan daya microwave dan lama waktu ekstraksi berpengaruh nyata terhadap parameter rendemen, total fenol, aktivitas antioksidan, dan kadar air. Hasil perlakuan terbaik didapatkan pada perlakuan daya microwave 400 W dengan waktu ekstraksi 2 menit yang menghasilkan rendemen 25,7%, total fenol 5,7 mg GAE/g, aktivitas antioksidan (IC50) 39 ppm dan nilai kadar air 72,4%.Kata kunci: antioksidan, ekstraksi, jahe merah, microwave-assisted extraction